Kumu Kahua Plays - Carroll, Dennis (University of Hawai'i Press, 1983)
In Hawaii an exciting tradition of local drama is reaching new audiences with plays that deal directly, often humorously, with life in this polychrome island state. The eight plays collected in this anthology celebrate the spirit of that tradition and offer an uninhibited feast for the ear - local language as it is spoken in contemporary Hawaii. In style and subject matter, the plays fall naturally into pairs: Ashes and Reunion are realistic dramas about problems of identity among the Japanese in Hawaii; Oranges Are Lucky and All Brand New Classical Chinese Theater add a touch of surrealism to their treatment of Chinese Americans; In the Alley and Paradise Tours depict the urbanized pressures of jet-age Hawaii at odds with older rhythms of life; and the last two plays, although written for a contemporary audience, draw on classical models- The Travels of Heikiki follows the structure of the historical pageant play, and the hugely popular Twelf Nite O Wateva! is a pidgin adaptation of Shakespeare's play. Carroll's introduction is a pioneering essay on the development of local drama that outlines the historical and theatrical context of these plays. The book is complete with a glossary of the pidgin words that appear in five of the eight plays.